Peran Kepemimpinan Sumber Daya Manusia Islam di Perguruan Tinggi Dalam Meningkatkan Produktivitas Pelayanan Akademik - Sudarmo; Gordius Ago (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The study in this research is to find out more about the role of Islamic Human Resources in high-level leadership to increase the productivity of academic services. The research method used is qualitative with the literature method. The literature taken comes from journals, books and other literature that is closely related to Human Resources in improving higher education. The results of the study show that Human Resources in the field of education are functional competencies possessed by educational staff in carrying out their duties which are required to actualize their abilities, both intellectual and physical abilities, in an integrated manner.